Efektivitas Pembelajaran Berbasis Praktikum Menggunakan Indikator Kertas Lakmus terhadap Pemahaman Konsep Asam–Basa Siswa - Putri Liya Ningsih; Puspa Pratiwi (Medan Resource Center, 2026)
Understanding acid–base concepts through practical laboratory activities remains an essential component of elementary science education because it enables students to connect theoretical knowledge with observable chemical phenomena. This study aimed to examine the effectiveness of litmus paper–based practical activities in facilitating students’ understanding of the acidic, alkaline, and neutral properties of commonly encountered household solutions. An experimental approach grounded in hands-on science learning was employed by testing lime solution, detergent solution, toothpaste solution, sugar solution, salt solution, and water using red and blue litmus paper indicators, while the resulting color changes were analyzed descriptively according to established acid–base principles. The findings revealed that lime solution exhibited acidic characteristics by changing blue litmus paper to red, whereas detergent and toothpaste solutions demonstrated alkaline properties by turning red litmus paper blue. In contrast, sugar solution, salt solution, and water produced no color change, indicating neutral characteristics. These findings demonstrate that litmus paper-based practical activities effectively facilitate students’ conceptual understanding of acid–base properties while strengthening basic science process skills through direct observation and experimental verification.